Effectivity Test of Ethanol Extract of Arabic Bidara Leaf (Ziziphus Spina-Christi L.) As Antibacterially Against Growt Bacteria Pseudomonas aeruginosa and Bacillus cereus - Vira Adiningsi; Amiruddin Eso; Yenti Purnamasari (MEDULA: Jurnal Ilmiah Fakultas Kedokteran Universitas Halu Oleo, 2024)
Background. Infection disease is one of the major health problems in developing countries including Indonesia, one of which is nosocomial infection caused by Pseudomonas aeruginosa bacteria. On the other hand, food poisoning is still a serious problem in Indonesia especially caused by pathogenic bacteria, one of which is Bacillus cereus bacteria. Indonesia is famous for its potential as home to medicinal plants. One plant that can potentially be used as an alternative in the treatment of this bacterial infection is arabic bidara leaves. This study aims to find out the effectiveness of arabic bidara leaf ethanol extract (Ziziphus spina-christi L.) as antibacterial against bacterial growth of Pseudomonas aeruginosa and Bacillus cereus. Methods. This study was an experimental study with a post test only control group design with a free variable in the form of treatment of arabic bidara leaf extract, a bound variable in the form of an inhibitory zone against Pseudomonas aeruginosa and Bacillus cereus. Positive control of ciprofloxacin and negative control using aquades. The concentrations used were 1500 ppm, 2000 ppm, 2500 ppm and 3000 ppm with three repetitions. Results. An ethanol extract of arabic bidara leaves has an inhibitory zone classified as strong at concentrations of 2000 ppm, 2500 ppm, and 3000 ppm. Conclusion. There is an antibacterial effectiveness of arabic bidara leaf ethanol extract against bacterial growth of Pseudomonas aeruginosa and Bacillus cereus. Keywords: Antibacterial, Bidara Arab Leaves, Pseudomonas aeruginosa, Bacillus cereus